Sperm morphology value in assisted reproduction: dismantling an enigma and key takeaways for the busy clinician - Christine Wyns; Paraskevi Vogiatzi; Ramadan Saleh; Rupin Shah; Ashok Agarwal (Therapeutic Advances in Reproductive Health)
The ideal morphology of the sperm cell was initially described based on the characteristics of sperm able to migrate through the endocervical canal assuming these had the best fertilization potential. Sperm morphology assessment has moved over the years toward stricter criteria based on the findings from studies that underline its value in successful reproductive outcomes. While treatment options are clear for some conditions related to abnormal sperm morphology, the value of sperm morphology in assisted reproduction requires further investigation. The objective of this review is to offer care providers updated guidance for choosing appropriate treatment strategies based on sperm morphology assessment and morphological deviations. Issues to be considered for a reliable determination and interpretation of sperm morphology using the current thresholds and criteria are discussed. In addition, key knowledge on morphological abnormalities relevant to the clinical care of infertile patients, distinguishing between monomorphic and polymorphic forms as well as the isolated or non-isolated occurrence of teratozoospermia in semen is presented. Furthermore, the impact of impaired morphology on assisted reproductive technique outcomes is summarized in light of the latest research.